Characterizing the length-dependence of DNA nanotube end-to-end joining rates. Issue 2 (6th January 2020) - Pacella, Michael S.; Mardanlou, Vahid; Agarwal, Siddharth; Patel, Anusha; Jelezniakov, Elizabeth; Mohammed, Abdul M.; Franco, Elisa; Schulman, Rebecca
Abstract : We experimentally characterize the length-dependence of the end-to-end joining rate of DNA tile nanotubes. We then test the ability of three different models of polymer end-to-end joining to reproduce experimentally measured changes in nanotube lengths during joining. Abstract : DNA nanotechnology offers a route towards the synthesis of custom nano-structured materials and circuits through hierarchical assembly processes. While predictive kinetic models are being developed for the assembly of DNA nanostructures from small monomeric components, a general model for the hierarchical assembly of DNA nanostructures remains elusive. DNA tile nanotubes provide an ideal model system for the study of hierarchical assembly via end-to-end joining. In this study, we experimentally characterize the length-dependence of the end-to-end joining rate of DNA tile nanotubes. We then test the ability of three different models of polymer end-to-end joining to reproduce experimentally measured changes in nanotube lengths during a joining reaction using an ODE model for nanotube joining. All three models predict physically realistic joining rates that are consistent with prior measurements, with a length-independent end-to-end joining rate model providing the best fit to the experimental data. A length-independent constant joining rate is consistent with other DNA self-assembly processes across a broad range of length scales and also suggests how tractable models for hierarchical DNA nanostructure could be developed.